Holy warriors : a modern history of the Crusades - Phillips, Jonathan (Jonathan P.) (New York : Random House, 2009)
From an internationally renowned expert, here is an accessible and utterly fascinating one-volume history of the Crusades, thrillingly told through the experiences of its many players--knights and sultans, kings and poets, Christians and Muslims.
"Deus vult!": the First Crusade and the capture of Jerusalem, 1095-99 -- "May God's curse be upon them!": relations between Muslims and Franks in the Levant, 1099-1187 -- "A woman of unusual wisdom and discretion": Queen Melisende of Jerusalem -- The "blessed generation": Saint Bernard of Clairvaux and the Second Crusade, 1145-49 -- Saladin, the Leper King, and the fall of Jerusalem in 1187 -- "Nowhere in the world would ever two such princes be found": Richard the Lionheart, Saladin and the Third Crusade -- "An example of affliction and the works of hell": the Fourth Crusade and the sack of Constantinople, 1204 -- From "little foxes in the vines" and the Children's Crusade to the greatest church council of the age -- "Stupor mundi": the wonder of the world: Frederick II, the Fifth Crusade and the recovery of Jerusalem -- "To kill the serpent, first you must crush the head": the crusade of Louis IX and the rise of the Sultan Baibars -- From the trial of the Templars to Ferdinand and Isabella, Columbus, and the conquest of the new world -- New crusaders?: from Sir Walter Scott to Osama bin Laden and George W. Bush.
Includes bibliographical references and index.
Keywords: Crusades; Middle East -- History; Europe -- Church history -- 600-1500.; Crusades -- Influence; Religion and civilization